2021
DOI: 10.3390/ph14070682
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Tyrosine Kinase Anti-Angiogenic Cediranib over Bevacizumab: Cell Cycle Abrogation and Synergy with Chemotherapy

Abstract: Angiogenesis plays a crucial role in tumor development and metastasis. Both bevacizumab and cediranib have demonstrated activity as single anti-angiogenic agents in endometrial cancer, though subsequent studies of bevacizumab combined with chemotherapy failed to improve outcomes compared to chemotherapy alone. Our objective was to compare the efficacy of cediranib and bevacizumab in endometrial cancer models. The cellular effects of bevacizumab and cediranib were examined in endometrial cancer cell lines using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…We have shown that supplementation with vitamin D improves the effectiveness of anti-angiogenic compound, cediranib, against A375 and SK-MEL-28 human melanoma cells, as we observed a marked decrease in melanoma cell proliferation (in both lines), G2/M cell cycle arrest, and a significant decrease in melanoma cell mobility (tested only in A375 melanoma cells). A similar observation was recently described in Hec50 cells, an endometrial adenocarcinoma, in which the combination of paclitaxel and cediranib produced a profound increase in the accumulation of cells in mitosis as assessed by the percentage of cells in G2/M by flow cytometry compared to paclitaxel alone (75). On the other hand, we did not observe any influence of vitamin D on proliferation of MNT-1 and RPMI-7951 melanoma cells treated with cediranib.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have shown that supplementation with vitamin D improves the effectiveness of anti-angiogenic compound, cediranib, against A375 and SK-MEL-28 human melanoma cells, as we observed a marked decrease in melanoma cell proliferation (in both lines), G2/M cell cycle arrest, and a significant decrease in melanoma cell mobility (tested only in A375 melanoma cells). A similar observation was recently described in Hec50 cells, an endometrial adenocarcinoma, in which the combination of paclitaxel and cediranib produced a profound increase in the accumulation of cells in mitosis as assessed by the percentage of cells in G2/M by flow cytometry compared to paclitaxel alone (75). On the other hand, we did not observe any influence of vitamin D on proliferation of MNT-1 and RPMI-7951 melanoma cells treated with cediranib.…”
Section: Discussionsupporting
confidence: 91%
“…Still, the authors concluded that the potential of cediranib may be enhanced in combination with other agents (68). Furthermore, it was shown recently on patient-derived organoid models of endometrial cancer that cediranib but not bevacizumab synergizes with chemotherapy, decreasing cell viability when combined with paclitaxel as compared to treatment with paclitaxel alone (75). Currently, there is an ongoing phase I clinical trial, NCT01364051, for patients with clinically unresectable solid tumors, including stage IV cutaneous melanoma and malignant melanoma, and for whom there is no standard therapy, in which patients are receiving cediranib with selumetinib, an oral MEK 1/2 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab is a humanized monoclonal antibody that inhibits vascular endothelial growth factor (VEGF). 11 , 12 A previous preclinical study demonstrated that plasma VEGF and tumor VEGF mRNA levels increased after erlotinib treatment in an NSCLC xenograft murine model. Increasing VEGF levels in tumors and plasma are associated with tumor progression and erlotinib resistance in an NSCLC xenograft murine model.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of multiple RTKs is an advantageous feature in cancer treatment. A study by Bi et al, 2021 has shown that cediranib combination with paclitaxel had higher cell death while bevacizumab combination with paclitaxel treatment showing a small insignificant change in cell death in endometrial cancer cells (102). In phase III trials, cediranib had limited benefit in metastatic colorectal cancer (NCT00384176), non-small cell lung cancer (NCT00795340), and recurrent glioblastoma (NCT00777153) (117)(118)(119).…”
Section: Investigatory Receptor Tyrosine Kinase Inhibitors In Clinica...mentioning
confidence: 99%
“…Furthermore, combining bevacizumab with various chemotherapies (paclitaxel and ixabepilone) in patients with TP53 mutations improved PFS and OS compared to chemotherapy alone ( 101 ). However, cediranib, an anti-angiogenic tyrosine kinase inhibitor, demonstrated higher cell cycle abrogation and synergy with chemotherapy compared to bevacizumab in endometrial cancer models in vitro ( 102 ).…”
Section: Therapeutics Targeting the Tumour Vasculaturementioning
confidence: 99%